The conversion code : stop chasing leads and start attracting clients - Smith, Chris, 1979- (John Wiley & Sons, Inc., 2022)
"The Conversion Code, 1st edition, taught real estate agents to engage with their prospective customers online first using social media, mobile apps, blogs and live chat, before ever meeting in-person. It quickly became one of the bestselling books on marketing and advertising real estated--with over 50,000 copies sold. This new revised edition includes updates on crucial new topics like TikTok and Instagram, and Virtual Staging, to help todays agents generate thousands of leads from social media and other digital sources, and turn those into closed sales."--